2005
DOI: 10.1179/174329305x19367
|View full text |Cite
|
Sign up to set email alerts
|

Feed forward control of back bead and bead height in narrow gap robotic welding

Abstract: For high quality welding, it is necessary to form a stable back bead and to melt metal plates. In narrow gap welding, it is difficult to control the bead height and the back bead simultaneously using conventional welding. In order to solve this problem, a switch back welding method is proposed in which the welding torch is moved back and forth along the welding line. In the forward movement of the torch, the arc heat is given to the root edges to obtain a wide back bead. In the backward movement, suitable bead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The authors obtained stable beads for large root gaps (between 2.3 mm and 4.9 mm and misalignments between 0.1 and 2.8 mm) in V-groove joints and without backing plates, through the continuous control of switchback technique parameters and GMAW process parameters. Based on this result, Yamane et al [4] carried out another work and proposed the use of the switchback technique to control bead height and root pass, but this time with narrow gap welding. They claimed that a stable back bead is formed, since the arc pre-heats the root edges when moving forwards.…”
Section: Introductionmentioning
confidence: 99%
“…The authors obtained stable beads for large root gaps (between 2.3 mm and 4.9 mm and misalignments between 0.1 and 2.8 mm) in V-groove joints and without backing plates, through the continuous control of switchback technique parameters and GMAW process parameters. Based on this result, Yamane et al [4] carried out another work and proposed the use of the switchback technique to control bead height and root pass, but this time with narrow gap welding. They claimed that a stable back bead is formed, since the arc pre-heats the root edges when moving forwards.…”
Section: Introductionmentioning
confidence: 99%
“…Gao and Wang [ 1 , 2 ] studied the effect of wire rotation on weld formation, especially lack of fusion in NGAW. Yao, Chen and Yamane [ 3 , 4 , 5 ] demonstrated that the process stability and weld morphology of NGAW could be improved by controlling the twisting and moving of the wire. Fan [ 6 ] found that twin-wire technique could improve arc stability, avoiding lack of fusion by adjusting wire feeding rate and wire distance.…”
Section: Introductionmentioning
confidence: 99%